2020
DOI: 10.1002/asna.202013831
|View full text |Cite
|
Sign up to set email alerts
|

NLTE C and O abundances in RR lyrae stars

Abstract: The high excitation levels that form the O i and C i lines seen in RR Lyrae stars have long been known not to obey local thermodynamic equilibrium (LTE) statistics. We have observed 21 RR Lyrae and related stars with the Apache Point Observatory echelle spectrograph on the 3.5‐m telescope and, for the first time, have derived abundances using non‐local thermodynamic equilibrium (NLTE) analyses in conjunction with spectral synthesis. In our previous investigation, we determined carbon to be overabundant using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…In our previous paper (Andrievsky et al 2020), we reported about decreased/or near-to-normal carbon abundance in a sample of 21 field RR Lyrae stars. We made a conclusion that no additional carbon is expected to be brought to the stellar surface after the He flash in the RR Lyrae core.…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…In our previous paper (Andrievsky et al 2020), we reported about decreased/or near-to-normal carbon abundance in a sample of 21 field RR Lyrae stars. We made a conclusion that no additional carbon is expected to be brought to the stellar surface after the He flash in the RR Lyrae core.…”
Section: Resultsmentioning
confidence: 90%
“…Microturbulent velocity was derived by avoiding dependence between iron abundance from individual Fe I lines and their equivalent widths. Finally, the gravity value was found by keeping equal mean iron abundances from Fe Andrievsky et al (2020). In Figures 1 and 2, we graphically show the procedure of T eff and V t determination for KX Lyr and RX Eri, and sensitivity of the adopted T eff and V t values to variations within ±150 K and ±0.2 km s −1 .…”
Section: Abundance Analysismentioning
confidence: 99%
See 3 more Smart Citations